Disappearance of correlations in the atom motion upon hydrogen intercalation into ReO3 lattice. (May 2016) - Timoshenko, Janis; Kuzmin, Alexei; Purans, Juris
Abstract: The influence of hydrogen intercalation on the local structure of rhenium trioxide is studied in-situ by the Re L3 -edge EXAFS spectroscopy and analysed using a novel approach, based on the use of evolutionary algorithm and wavelet transform. The proposed method allows us to perform accurate EXAFS analysis within the multiple-scattering approach taking into account contributions from outer coordination shells and to access the information on correlations in atomic thermal motion.